A study of population of weed on direct seeded rice planting system / Noor Asmanizan Seman - Seman, Noor Asmanizan (Faculty of Plantation and Agrotechnology, 2019)
Weed is well known as the main competitor in a rice field and excessive weed lead to the reduction of rice yield as it competes with rice in terms of space, nutrients and also as a nesting place for the pest. The composition of the weed in the rice field been identified becomes wider after the direct seeded rice planting system applied since 1985. Hence, the survey had been done at MR2202CL rice field that applying the direct seeded planting system, to know the population of weed that exist and the most abundance weed. The method use for the data collection is the sampling technique using quadrat method with systematically sampling. The frequency, relative frequency, density and relative density was identify. The outcome from the data collected during the field survey, there are six diverse species of 5 family which were Cyperaceae, followed by Onagrace, Pontederiaceae, Lentibulariaceae and Poaeceae The outmost weeds in the field based on the relative frequency is Monochoria vaginalis with 78.95% meanwhile the one that have the highest density is Ludwigia octovalvis which the relative density is 31.25%. Both weed should be the main attention while choosing the right herbicide so that the application of the herbicide are effective.